Bound states and atomic interaction in giant atom waveguide QED with dispersive coupling - Mingzhu Weng; Zhihai Wang (Results in Physics)
In this paper, we investigate the bound states and the effective interaction between a pair of giant atoms, which couples to the coupled resonator waveguide in a nested configuration. To suppress the harmful individual and collective dissipations to the waveguide, we consider the dispersive coupling scheme, where the frequency of the giant atoms are far away from the propagating band of the waveguide. In our scheme, the atomic interaction can be induced by the overlap between the bound states in the gap. We demonstrate the relative position dependent atomic coupling and explore its application in the state transfer. We find that the transfer fidelity of a superposition state can approach 0.999. Therefore, our scheme is useful for designing robust quantum information processing.